NZSS 1900 Model Building By-law: a planned evolution - Isaacs, Nigel (Architectural History Aotearoa, 2022)
Twenty-five years after its publication, NZSS 95:1935 "Model Building By-law" was starting to show its age. The 1961 City Engineers conference requested it be reorganised to put general requirements first and design requirements later. The NZ Standards Institute's (NZSI) Bylaw Sectional Committee thought this a good idea, although to avoid confusion changed the designation of the new series to NZSS 1900. From late 1963 to mid-1964, NZSS 95 was reissued as NZSS 1900. The 14 parts of NZSS 95 became 11 chapters of NZSS 1900, initially by reprinting with new covers. Over the next 20 years the chapters were modified, revised, split, or amalgamated. On 1 April 1966 NZSI became the Standards Association of New Zealand (SANZ), and 'New Zealand Standard Specifications" (NZSS) became "New Zealand Standards" (NZS). By late 1966 the revision and publication of NZS 1900 was nearly complete. For the future a five yearly review cycle was planned. However, storm clouds were ahead. NZS 1900 had a mixture of: legal requirements; design and construction requirements; quantitative requirements; and codes of practice. The resultant documents were considered to be hard to: use; inspect on site; and revise. In late 1969 the Standards Council was looking forward to a revision separating requirements (fixed, unchanging and rarely alternative) from solutions (changing as technology develops, often with alternatives). The "means of compliance" could be provided for the majority of users, while other solutions were available as desired or required. This set the scene for the Building Act 1991 and New Zealand Building Code. The paper reviews the development of NZS 1900, exploring the similarities and differences to NZSS 95. As an example of the process, the evolution of the requirement for windows for ventilation will be examined.